The Influence of Information Quality, Facilities, and Alumni on the Decision to Choose a WBI Polytechnic Campus Through Brand Image as an Intervening Variable - Muhammad Roestian Fahmi Nasution; Sugiharto Pujangkoro; Beby Karina Fawzeea Sembiring (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Wilmar Bisnis Indonesia Polytechnic (WBI) is an educational institution committed to becoming the best and ideal educational institution for Indonesia's young generation to be ready to compete in the increasingly competitive business world in the industrial era 4.0. One of the factors that can make prospective students decide to choose to study at the WBI Polytechnic includes the Quality of Information, Facilities, Alumni, and Brand Image. This study aims to determine the effect of the quality of information, facilities, and alumni on the decision to choose a WBI Polytechnic Campus through Brand Image as an Intervening Variable. The population in this study were active students in the 2019, 2020 and 2021 batches, totaling 396 students and the sample with the criteria for class 2021 students totaling 123 students. Data collection methods were carried out by means of interviews, questionnaires, and documentation studies. Methods and techniques of analysis of multiple regression using path analysis (path analysis). The results of the research on the direct effect on the first substructure state that simultaneously and partially, Information Quality, Facilities, and Alumni have a positive and significant effect on Brand Image. The results of the research on the direct effect on the second substructure state that simultaneously and partially, Information Quality, Facilities, Alumni, and Brand Image have a positive and significant effect on Voting Decisions. The results of the indirect effect study stated that Information Quality, Facilities, and Alumni had a positive and significant effect on Voting Decisions through Brand Image as an intervening variable.